2002
DOI: 10.1111/j.1346-8138.2002.tb00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Gluco‐Oligosaccharide against Staphylococcus aureus

Abstract: Heavy colonization of atopic dermatitis (AD) with Staphylococcus aureus is well documented. The purpose of the present study is to examine the actions of gluco-oligosaccharide (G-OS) against S. aureus for the control of AD skin lesions infected with S. aureus. The colony counts of S. aureus cells in 0.5% sodium chloride solution supplemented with 5% G-OS (pH 4.8) were about 10-fold lower than those in 0.5% sodium chloride solution (pH 6.6; control) after incubation for 24 hours. The colony counts of S. aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Commensal bacteria contribute to a healthy skin microflora by inhibiting colonization and biofilm formation of pathogenic bacteria on the skin (36). It has been shown that topical application of gluco-oligosaccharides was successful in controlling Staphylococcus aureus colonization of AD skin (37). In cosmetics, prebiotics have the potential to increase selectively the activity and growth of beneficial skin microflora (38); the maintenance of a balanced microbiome does also contribute to an optimal and functional skin barrier (39).…”
Section: Discussionmentioning
confidence: 99%
“…Commensal bacteria contribute to a healthy skin microflora by inhibiting colonization and biofilm formation of pathogenic bacteria on the skin (36). It has been shown that topical application of gluco-oligosaccharides was successful in controlling Staphylococcus aureus colonization of AD skin (37). In cosmetics, prebiotics have the potential to increase selectively the activity and growth of beneficial skin microflora (38); the maintenance of a balanced microbiome does also contribute to an optimal and functional skin barrier (39).…”
Section: Discussionmentioning
confidence: 99%
“…aureus colonizes the wounds in the form of a biofilm that is not treatable with antibiotics (Katsuyama et al, 2005) and only the action of polymorphonuclear leukocytes which is capable of destroying this biofilm (Akiyama et al, 2002). The problem with infection by PVL-positive S. aureus is that leukocytes are destroyed by the PVL which explains the complication of these infections being difficult to treat.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been suggested that antibiofilm therapies that target the entire biofilm as a complex multicellular organism or prevent unique, biofilm-specific processes, are needed to fight biofilm infections [57]. Future directions in therapeutics may include chemical synthesis and the use of quorum-sensing molecules to prevent microbial cell-to-host and microbial cellto-microbial cell attachment, or promote cell detachment from mucosal surfaces or biofilms.…”
Section: Therapeutic Challenges In Mucosal Biofilm Infectionsmentioning
confidence: 99%
“…In addition, the combination of locally delivered proinflammatory cytokine-based therapeutics with traditional antimicrobial drugs may be a reasonable future approach to treatment. For example, agents that promote invasion of phagocytic cells into the biofilm, in combination with glycocalyxreducing drugs, may increase the effectiveness of treatment in biofilm-associated skin infections [57]. Along these lines, the beneficial effects of a granulocyte-macrophage colonystimulating factor-based mouthrinse was shown recently in radiation-treated patients with pseudomembranous candidiasis [59].…”
Section: Therapeutic Challenges In Mucosal Biofilm Infectionsmentioning
confidence: 99%